Clinical evaluation of a Hepatitis C Virus whole-genome sequencing pipeline for genotyping and resistance testing. (March 2022) - Bradshaw, Daniel; Bibby, David F.; Manso, Carmen F.; Piorkowska, Renata; Mohamed, Hodan; Ledesma, Juan; Bubba, Laura; Chan, Yuen T.; Ngui, Siew Lin; Carne, Simon; Mbisa, Jean L.; ,
Abstract: Objectives: We sought to evaluate clinically a hepatitis C virus (HCV) whole-genome, next-generation sequencing (NGS) pipeline that is agnostic to viral genotype. Methods: Performance of the NGS pipeline was assessed through comparison of results with Sanger sequencing (SS) of partial HCV genomes. Results: There was 98.7% (376/381) concordance for viral subtype between SS and NGS. The positive and negative per cent agreements for determination of resistance-associated substitutions were 97.8% (95% CI 92.5–99.4%) and 99.9% (95% CI 99.5–100.0%), respectively. The NGS pipeline was also able to detect novel subtypes, mixtures, recombinants, transiently occurring resistance mutations and distinguish re-infection with the same subtype from relapse. Discussion: Particular scenarios where NGS may be used include settings without universal access to pan-genotypic antiviral regimens, those infected with a 'rare' subtype or who have been failed by first-line therapy, and in cases of suspected re-infection.